Structural analysis of basalt fiber reinforced plastic wind turbine blade - Mengal, A.N. (EDP Sciences, 2014)
In this study, Basalt fiber reinforced plastic (BFRP) wind turbine blade was analyzed and compared with Glass fiber reinforced plastic blade (GFRP). Finite element analysis (FEA) of blade was carried out using ANSYS. Data for FEA was obtained by using rule of mixture. The shell element in ANSYS was used to simulate the wind turbine blade and to conduct its strength analysis. The structural analysis and comparison of blade deformations proved that BFRP wind turbine blade has better strength compared to GFRP wind turbine blade. Â© 2014 Owned by the authors, published by EDP Sciences.